Effect Of Governance, Capital Structure, And CSR On Firm Value With Family Ownership As A Moderator In IDX Manufacturing Companies - Namira Mudrikah Rahmadhina; Abdillah Arif Nasution; Narumondang Bulan Siregar (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of corporate governance, capital structure, and Corporate Social Responsibility (CSR) on firm value, with family ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. Firm value is measured using Price to Book Value (PBV), while the independent variables consist of GCG, Debt to Equity Ratio (DER), and the 2021 GRI-based CSR disclosure index. Family ownership is used as a moderating variable to determine the extent to which family control can strengthen or weaken the relationship between the independent variables and firm value. The research method uses a quantitative approach with panel data. The sample was obtained through a purposive sampling technique, with a total of 50 family manufacturing companies, resulting in 290 observations over the four years 2021–2024. Data analysis was performed using panel data regression. The research model was declared feasible based on the F-test results with a probability value of 0.000000. The adjusted R-squared value of 0.847644 indicates that the independent and moderating variables are able to explain 84.76% of the variation in firm value. The results indicate that corporate governance, capital structure, and CSR partially have a positive and significant effect on firm value. Family ownership also proved to have a positive and significant effect on firm value. Furthermore, family ownership moderates and strengthens the relationship between corporate governance and firm value, indicating that dominant family ownership encourages more effective implementation of GCG principles. These findings imply that manufacturing companies, particularly family-owned companies, need to strengthen governance, optimally manage their capital structure, and consistently increase CSR disclosure to enhance firm value.